Comparison Between Unit Cost Results of The ABC Method And INA-CBGs Rates For BPJS Patients With Caesarea Sectio Action at Rumah Sakit Graha Sehat Probolinggo - Susanti Sugianto; Yanuar Ramadhan; Erry Yudhya Mulyani; Rokiah Kusumapradja; Nofierni Nofierni (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Delivery using the caesarean section method is one of the JKN-KIS services which has experienced a significant increase in cases from year to year at Graha Sehat Probolinggo Hospital. The general tariff applied by the hospital is IDR 10,800,000, which is 206.15%, far above the INA CBGs tariff of IDR 5,238,800, making the hospital feel the need to carry out descriptive quantitative research using the ABC method and DD method. Then the unit cost results of the ABC method are compared with the INA-CBGs rates. The results of this research show that the unit cost of the ABC method is IDR 5,484,214, which is IDR 245,414 (4.68%) greater than the INA-CBGs tariff. The potential efficiency that can be achieved results in savings of IDR 665,295 so it is hoped that the unit cost of the ABC method will be IDR 4,818,919. IDR 419,881 (8.01%) smaller than the INA-CBGs tariff. The conclusion is that there is a negative difference between the unit costs of the ABC method and the DD method and the INA CBGs rates. Hospitals should submit a tariff review to BPJS, including a review of the provision of separate tariffs for baby handling costs. Apart from that, hospitals also need to make efficiencies by reducing length of stay, reviewing medical services, efficiency in laundry units and CSSD, speeding up RME, as well as efficiency in several other resources while still prioritizing patient safety